Enhancing Teacher Competencies For Educational Excellence (A Case Study At Dayah Babul Mustaqim Bireuen District) - Mulyadi Abdisas; Iskandar; Fauzan Ahmad Siregar (Journal Informatic, Education and Management (JIEM), 2025)
This study explores the development of teacher competencies at Dayah Babul Mustaqim Bireuen, with a focus on how these competencies contribute to improving the quality of education in the institution. The main objectives were to identify the strategies used in enhancing teacher skills and to evaluate their impact on the overall educational process. A qualitative descriptive approach was employed, using semi-structured interviews with school leaders and teachers, focus group discussions with students, and classroom observations. The findings revealed that teacher competency development at Dayah Babul Mustaqim involves strategic planning, needs identification, and the implementation of training programs, which have significantly contributed to the improvement of teaching methods and learning outcomes. Teachers reported positive changes in their pedagogical approaches, including the adoption of more interactive and student-centered teaching strategies. The research also highlighted the role of professional development programs, such as peer mentoring and independent training, in boosting teacher confidence and effectiveness. The results underscore the importance of continuous teacher development in enhancing both personal teacher growth and overall educational quality. This study provides valuable insights into the role of teacher competency development in Islamic education settings, offering recommendations for other institutions facing similar challenges.